Tunable S-band output based on Raman shift in dispersion shifted fiber - Ahmad, H. (Taylor & Francis, 2013)
A tunable short-wavelength band Raman fiber laser using a dispersion shifted fiber as the nonlinear medium is proposed and demonstrated. This approach provides an alternative to the common method of using depressed-cladding, erbium-doped fibers as the gain medium in S-band fiber lasers. The proposed laser has a tuning range of 1508 to 1534 nm as well as an average peak power of about −11.3 dBm within the range 1518–1530 nm. A high signal-to-noise ratio of approximately 70 dB is obtained from the system at this range.